Polymerization‐Induced Self‐Assembly of Functionalized Block Copolymer Nanoparticles and Their Application in Drug Delivery - Zhang, Wen‐Jian; Hong, Chun‐Yan; Pan, Cai‐Yuan (Macromolecular rapid communications., 2019)
Drug delivery systems (DDS) based on functionalized polymeric nanoparticles have attracted considerable attention. Although great advances have been reported in the past decades, the fabrication efficiency and reproducibility of polymeric nanoparticles are barely satisfactory due to the intrinsic limitations of the traditional self‐assembly method, which severely prevent further applications of the intelligent DDS. In the last decade, a new self‐assembly method, which is usually called polymerization‐induced self‐assembly (PISA), has become a powerful strategy for the fabrication of the polymeric nanoparticles with bespoke morphology. The PISA strategy efficiently simplifies the fabrication of polymeric nanoparticles (combination of the polymerization and self‐assembly in one pot) and allows the fabrication of polymeric nanoparticles at a relatively high concentration (up to 50 wt%), making it realistic for large‐scale production of polymeric nanoparticles. In this review, the developments of PISA‐based polymeric nanoparticles for drug delivery are discussed. Drug delivery systems based on functionalized polymeric nanoparticles have attracted considerable attention. For fabrication of polymeric nanoparticles, polymerization‐induced self‐assembly (PISA) offers decisive advantages over conventional protocols in terms of efficiency and cost‐effectiveness. Recently, the nascent investigation of functional PISA‐generated nanocarriers with stimulus‐responsive drug release has already found applications in the biomedical area, which is discussed in this review.